Fetal myocarditis - a precursor of undesirable consequences of intrauterine infection with parvovirus B19 - N. P. Bondarenko; V. M. Zhezhera; A. V. Aksonova (Zaporozhye State Medical University, 2019)
Objective: to conduct a retrospective analysis of the results of sonographic, virological and morphological studies of cases of non-immune hydrops fetalis followed by intrauterine fetal death because of severe cardiovascular insufficiency (SCI) against parvovirus infection (PVI) with the aim of identifying signs of an adverse perinatal prognosis for the fetus. Object and methods. Infection of pregnant women was detected by serological diagnostics of specific antibodies IgM and IgG to parvovirus B19. Intrauterine fetal infection was confirmed by polymerase chain reaction (PCR). An antenatal diagnosis of hydrops fetalis was made using ultrasound scanning; intracranial hemodynamics, fetal myocardial hemodynamics and heart function were monitored using Doppler ultrasound with calculation of peripheral vascular resistance indices. The myocardium of human fetus was studied histologically with hematoxylin and eosin staining. Results. In 15/33 (45.5 %) cases of infection with parvovirus B19 non-immune fetal hydrops was diagnosed in the II-III trimesters of pregnancy. The development of CVI, which arose secondary, against the background of myocarditis with/without fetal anemia (FA) was found in all the cases of fetal loss - 6/15 (40 %), in which the presence of parvovirus DNA in the pericardial effusion was proven after autopsy by the results of a polymerase chain reaction. Conclusions. Myocarditis as a result of PVI promotes the emergence of CVI with the development of hydropericardium, has a fatal prognosis for the fetus, despite attempts to intrauterine blood transfusion in the III trimester. Fetal myocarditis against the background of non-immune fetal hydrops hinders timely non-invasive diagnosis of severe FA, is the cause of CVI which leads to extremely unfavorable consequences for the fetus.